The impact of sign language and speech translators on the MFD community: a statistical analysis - Bilal, Sara Mohammed Osman Saleh; Shuriye, Abdi Omar; Akmeliawati, Rini (Centre for Promoting Ideas, USA, 2012)
This research introduces a survey on the impact of the existing and developed Automatic Sign Language Translator (ASLT) and Speech Translator (ST) systems on the hearing/speech impaired societies. The objective of the study is to examine whether these automatic systems are able to split the communication barriers between hearing/speech impaired people and hearing people. Essentially, the research explores the out come of the survey which was conducted in collaboration with the Malaysian Federation Deaf (MFD) society in Malaysia. The significant of this research lies in the fact that it serves exceptional human course. Data and information collected are systematically organized for reliability purposes.